Case of pemphigoid vegetans with autoantibodies against the BP180 C‐terminal domain and BP230 antigen. Issue 8 (18th May 2021) - Doi, Chiaki; Shiraishi, Ken; Koga, Hiroshi; Ishii, Norito; Sayama, Koji
Abstract: Pemphigoid vegetans is a rare variant of bullous pemphigoid characterized by vegetative and purulent lesions of the groin, axillae, thighs, hands, eyelids, and perioral regions. The clinical features and histological findings of pemphigus vegetans and immunohistochemical characteristics of bullous pemphigoid are shown. An 86‐year‐old woman presented with vegetative lesions in the vulva and groin, and blisters on the head, neck, axillae, and thighs. Although clinically suspected as pemphigus vegetans, skin biopsy showed subepidermal clefts with eosinophil infiltration and eosinophilic pustules in the epidermis. Direct immunofluorescence analysis showed linear deposition of immunoglobulin (Ig)G along the basement membrane zone. Indirect immunofluorescence using 1 mol/L NaCl salt‐split skin showed linear deposition of IgG on the epidermal side. Chemiluminescent enzyme immunoassay and enzyme‐linked immunosorbent assay were positive for BP180 and BP230. Immunoblotting of recombinant protein of the BP180 C‐terminal domain showed positive reactivity. Pemphigoid vegetans was diagnosed and treated successfully with oral corticosteroids. This is the first case of pemphigoid vegetans reported to date with detection of autoantibodies against both BP180 C‐terminal domain and BP230.